1993
DOI: 10.1021/bi00093a010
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium NMR studies of the effect of pulmonary surfactant SP-C on the 1,2-dipalmitoyl-sn-glycero-3-phosphocholine headgroup: A model for transbilayer peptides in surfactant and biological membranes

Abstract: Surfactant protein C (SP-C) was isolated from solvent extracts of porcine pulmonary surfactant by gel filtration chromatography. The surfactant protein was combined with dipalmitoylphosphatidylcholine deuterated at the alpha and beta positions of the choline headgroup (DPPC-d4) Deuterium nuclear magnetic resonance spectra were collected as a function of temperature for a series of protein concentrations. The splitting of the alpha-deuteron spectrum in the liquid-crystalline phase was insensitive to temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 26 publications
4
32
0
Order By: Relevance
“…4B, the evolutionarily strictly conserved Lys-Arg dipeptide segment in positions 11-12 [39] is suitably located for interacting with the phosphatidyl choline moieties of DPPC. This would also be in agreement with deuterium NMR studies of selectively deuterated DPPC preparations containing variable amounts of SP-C, which provided evidence for direct interactions between the positive charges of SP-C and the lipid headgroups [40]. Furthermore, the palmitoylcysteinyls at positions 5 and 6 are then located near the exterior surface of the DPPC bilayer (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…4B, the evolutionarily strictly conserved Lys-Arg dipeptide segment in positions 11-12 [39] is suitably located for interacting with the phosphatidyl choline moieties of DPPC. This would also be in agreement with deuterium NMR studies of selectively deuterated DPPC preparations containing variable amounts of SP-C, which provided evidence for direct interactions between the positive charges of SP-C and the lipid headgroups [40]. Furthermore, the palmitoylcysteinyls at positions 5 and 6 are then located near the exterior surface of the DPPC bilayer (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…The hydrophobic surfactant protein, SP-B has been shown to have positively charged amphiphatic alpha-helices that can interact strongly with the anionic phosphatidylglycerol (PG) lipid head-groups in model membrane bilayers (Longo et al, 1992). SP-C also has positive charges in its N-terminal region which is associated with the lipid head-groups in bilayers (Morrow et al, 1993). It seems therefore likely that electrostatic interaction will associate BSA with the SP-B and SP-C of the BLES bilayers.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence measurements indicate that SP-C increases rigidity in the phospholipid head group region but disrupts the interior acyl-chain packing of the bilayer (Horowitz et al, 1992) and that the N-terminus is located in the vicinity of the membrane surface (Horowitz et al, 1993). 'H-NMR spectrosocpy showed that the positively charged amino acids in the N-terminal part of porcine SP-C are located close to the phospholipid head group (Morrow et al, 1993b). No experimental information about the orientation in the membrane of the palmitoyl chains is available.…”
Section: Structures Interactions and Dynamics In Relation To Functiomentioning
confidence: 99%